2018
DOI: 10.1097/eja.0000000000000761
|View full text |Cite
|
Sign up to set email alerts
|

Lung recruitment prevents collapse during laparoscopy in children

Abstract: NCT02824146.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
68
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(75 citation statements)
references
References 31 publications
2
68
1
4
Order By: Relevance
“…18 Therefore, all strategies to pre- conducted both in adults and in children. 2,11,21 In the current study, children were overly exposed to lung de-recruitment (use of ZEEP or low level of PEEP, high FiO 2 , extubation while apply suctioning) and only 20% of the intubated patients received recruitment maneuvers. 22 Habre et al recommend to set the FiO 2 at 80% during emergence in children as a compromise between the consequences of high FiO 2 and the increased risk of desaturation in younger children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Therefore, all strategies to pre- conducted both in adults and in children. 2,11,21 In the current study, children were overly exposed to lung de-recruitment (use of ZEEP or low level of PEEP, high FiO 2 , extubation while apply suctioning) and only 20% of the intubated patients received recruitment maneuvers. 22 Habre et al recommend to set the FiO 2 at 80% during emergence in children as a compromise between the consequences of high FiO 2 and the increased risk of desaturation in younger children.…”
Section: Discussionmentioning
confidence: 99%
“…These experts in pediatric mechanical ventilation nowadays recommend the following: avoidance of a high tidal volume, monitoring expired tidal volume and end-tidal CO 2 (EtCO 2 ) and using a low inspired fraction of oxygen (FiO 2 ), a positive end-expiratory pressure (PEEP), and recruitment maneuvers, but also avoidance of unnecessary tracheal suction in order to prevent atelectasis formation (see Appendix B). [5][6][7][8][9][10][11] In the absence of a high level of evidence for optimal ventilation criteria in anesthetized children with healthy lungs, the aim of the present study was to assess current ventilatory management practice during pediatric anesthesia in France, looking specifically at the parameters defined in the above-mentioned expert statements and with a specific focus on tidal volume.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that a more aggressive PEEP level is required to reduce shunt and to normalize respiratory compliance during laparoscopic surgery because of the reduction of FRC caused by the pneumoperitoneum . Acosta et al suggested that PEEP levels higher than the usual 5 cmH 2 O would be required to preserve normal lung aeration during pneumoperitoneum in pediatric laparoscopic surgeries . However, these higher levels of PEEP must be matched with the patients' hemodynamics that appear to be more sensitive to airway pressure than in adults .…”
Section: Discussionmentioning
confidence: 65%
“…A decrease in R5 suggests an improved Cdyn. Although the effect of ARMs on lung compliance is controversial [13], many studies have reported a statistically significant increase in lung compliance after ARMs in patients undergoing surgery [2,[12][13][14][15]. We hypothesized that respiratory resistance would be a better parameter for measuring the effects of ARMs in patients with intact respiratory systems; however, this hypothesis was incorrect.…”
Section: Discussionmentioning
confidence: 98%
“…Using recruitment maneuvers to open the lungs improves the effectiveness of PEEP for gas exchange during mechanical ventilation [9][10][11]. Although many studies have reported the effectiveness of low tidal volume ventilation and ARMs [2][3][4][12][13][14][15], no studies have evaluated ARMs independently of the PEEP level [16]. The definition of ARMs varies among studies.…”
Section: Introductionmentioning
confidence: 99%